Deepening Trochleoplasty With a Thick Osteochondral Flap for Patellar Instability: Clinical and Functional Outcomes at a Mean 6-Year Follow-up. (November 2015) - McNamara, Iain; Bua, Nelson; Smith, Toby O.; Ali, Khameinei; Donell, Simon T.
Background: In patients with patellar instability and severe trochlear dysplasia, trochleoplasty has become increasingly used as part of its surgical management. Hypothesis: Deepening trochleoplasty for severe dysplasia in patellofemoral instability improves function and increases sports participation. Study Design: Case series; Level of evidence, 4. Methods: Between 1995 and 2010, deepening trochleoplasty with a thick flap was performed in 90 patients (107 knees) with severe trochlear dysplasia. Data were collected prospectively preoperatively, at 6 weeks, and at 1-year follow-up. The patients were surveyed retrospectively to determine the clinical and functional outcomes including sports and exercise participation at a minimum of 2 years, with complete data available in 92%. Results: The average follow-up was 6 years (range, 2-19 years). The median Kujala score was 63 (interquartile range [IQR], 47-75) preoperatively, rising to 79 (IQR, 68-91) at 1-year follow-up and 84 (IQR, 73-92) at final follow-up ( P < .05). Seventy-two percent were satisfied with their knee function at 1-year follow-up, rising to 83% at final follow-up ( P < .0001). Sports and exercise participation increased from 36 patients (40%) preoperatively to 60 (67%) at final follow-up. The number of patients involved in competitions increased slightly from 10 (11%) to 11 (12%). Of those sports that involved twisting (eg, soccer, cricket, badminton), the number of patients participating increased from 16 (18%) to 22 (24%), whereas in nontwisting sports (eg, running, swimming, cycling), it increased from 24 (27%) to 47 (52%), of whom 12 (16%) used walking as exercise. Two patients who had undergone medial patellofemoral ligament (MPFL) reconstruction as the index operation needed the MPFL revised, and a further 8 patients needed MPFL reconstruction subsequently for instability symptoms and a mediolateral glide in extension of more than 2 quadrants' displacement. At final follow-up, no patient had mechanical patellofemoral instability. Conclusion: Deepening trochleoplasty with a thick flap improves clinical and functional outcomes for patients with symptomatic patellar instability with severe trochlear dysplasia. These results improve over time and beyond 1-year clinical follow-up. However, trochleoplasty does not lead to a significant improvement in sports participation at a competitive level. It does improve patient participation in sports and exercise, principally in nontwisting sports activities.